Peningkatan hasil belajar Gerak lokomotor dengan pendekatan bermain siswa sekolah dasar kelas 1 SD Tahfidz griya qurany - ‘Ala, Faridatul; Candra, Juli; Rahmalia, Apriyanti; Hakim, Lukman (Journal of Professional Elementary Education, 2025)
Improvement of locomotor movement learning outcomes with a play approach for grade 1 elementary school students of SD Tahfidz Griya Qurany. Thesis. Faculty of Education. Bhayangkara University, Greater Jakarta. The researcher aims to improve the learning outcomes of locomotor movements (walking, running, jumping) of grade I students of SD Tahfidz Griya Qurany, Bekasi Regency, by using a play approach. The research method used is the Action Research method, Action research uses cycles, where each cycle has systematic steps consisting of action planning, implementation, observation and reflection. Based on the results of the research on classroom actions that have been carried out in 2 (two) cycles in this study, it can be concluded that: 1. The application of the play approach can improve the locomotor movement ability of students. 2. The data on the completeness of locomotor motion learning in the first cycle of the first meeting reached 33.33% and in the second meeting reached 41.67%. Meanwhile, in the second cycle, the first meeting reached 50% and in the second meeting, it reached 95.83%. 3. The application of the play approach can improve the learning outcomes of locomotor movements in grade I students of SD Tahfidz Griya Qurany for the 2024/2025 school year